Silicon carbide ceramic material with super-compact surface layer and preparation method thereof
By sealing the pores through surface treatment and chemical vapor deposition after sintering, the problem of a large number of pores in silicon carbide ceramic materials during the sintering process is solved, and the surface layer is super-densified and the performance is improved.
Patent Information
- Application Number
- CN202411413377.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-21
AI Technical Summary
The existing silicon carbide ceramic materials have a large number of porosities during the sintering process, which cannot achieve low porosity, and isostatic sintering equipment has high requirements and cannot be completely void-free.
The pores are sealed by surface treatment after sintering. The steps of blank preparation, pre-sintering and surface sealing are used, combined with the chemical vapor deposition method to seal the pores to form an ultra-dense silicon carbide ceramic material on the surface.
It achieves ultra-densification of the silicon carbide ceramic surface layer, reduces porosity, increases density, hardness, strength and thermal conductivity, and extends service life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silicon carbide ceramics and preparation processes, and in particular relates to a surface ultra-dense silicon carbide ceramic material and a preparation method. Background Art
[0002] Silicon carbide ceramics have been widely used at present because of their significant practicality. In terms of the existing firing level, the current silicon carbide ceramics have many advantages, such as extremely strong oxidation resistance, high high temperature strength, good wear resistance, high hardness, etc. In traditional pressureless sintered silicon carbide ceramics, due to the mutual fusion and growth between ceramic powder particles during the sintering process, there are a large number of pores in the ceramic body, and it is impossible to achieve low porosity of silicon carbide ceramics. Although isostatic pressing can reduce the porosity of ceramics, its equipment requirements are relatively high and it is impossible to achieve complete void-free. Therefore, in order to meet the requirements of certain usage scenarios for ultra-dense, high hardness and low porosity of silicon carbide ceramic surfaces, the present invention proposes a surface ultra-dense silicon carbide ceramic material and a preparation method. Summary of the invention
[0003] Technical solution: In order to solve the above technical problems, the present invention provides a surface ultra-dense silicon carbide ceramic material, which is made by first sintering silicon carbide powder and then sealing the pores through surface treatment to make the surface ultra-dense silicon carbide ceramic material.
[0004] As an improvement, the porosity of the surface ultra-dense silicon carbide ceramic material is less than 0.1%, and the density is 2.8-3.2 g / cm 3 , surface hardness is 2000~3000kg / mm 2 , three-point bending strength 250~300MPa, thermal conductivity 100~130W / (m·K), thermal expansion coefficient (3~5)×10 -6 / K.
[0005] At the same time, a method for preparing a surface ultra-dense silicon carbide ceramic material is also provided, comprising the following sequential steps:
[0006] (1) Powder preparation
[0007] (1.1) Mixing the raw material silicon carbide and the binder according to a certain proportion to obtain a mixed powder;
[0008] (1.2) Grinding the mixed powder in a grinder to obtain fine powder with an average diameter of 20 to 300 μm;
[0009] (2) Slurry preparation
[0010] (2.1) adding a dispersant, a surfactant, a defoaming agent and a solvent to the fine powder obtained in step (1.2);
[0011] (2.2) stirring the mixture in step (2.1) to form a slurry;
[0012] (3) Preparation of green billet
[0013] (3.1) adding the slurry in step (2) into a mold and pressing and drying to form a ceramic green body;
[0014] (3.2) heating and drying the green blank in step (3.1) at a drying temperature of 50 to 300° C. for a drying time of 0.1 to 2 h;
[0015] (4) Pre-sintering
[0016] Pre-sintering the dried green blank in step (3) at a temperature of 800 to 1300° C. for a sintering time of 1 to 8 hours;
[0017] (5) Surface sealing
[0018] (5.1) The pre-sintered green blank in step (4) is placed in a vacuum impregnation tank and evacuated to a vacuum degree of 0.5 to 1.5 MPa; (5.2) The polycarbosilane solution is introduced into the impregnation tank in step (5.1) and the vacuum degree is maintained for 0.5 to 5 hours;
[0019] (5.3) taking out the impregnated green body in step (5.2), and drying it at 80-200° C. for 1-5 hours to remove the solvent;
[0020] (5.4) placing the dried green blank in step (5.3) into a chemical vapor deposition furnace, evacuating the furnace to a vacuum degree of 0.8 to 1.5 MPa, and maintaining the vacuum degree;
[0021] (5.5) heating the chemical vapor deposition furnace in step (5.4) to 800° C. at a rate of 5 to 10° C. / min and maintaining the temperature for 0.5 to 2 h;
[0022] (5.6) introducing argon gas into the chemical vapor deposition furnace of step (5.5) at a flow rate of 10 to 200 ml / min;
[0023] (5.7) After the argon gas is passed through step (5.6) for 10 to 30 minutes, a mixture of hydrogen and chloroform is passed through the chemical vapor deposition furnace;
[0024] (5.8) heating the chemical vapor deposition furnace in step (5.7) to 900-1300° C. at a rate of 1-5° C. / min and keeping the temperature for 1-5 h;
[0025] (5.9) After step (5.8) is completed, stop introducing hydrogen and chloroform, and cool the furnace to 100°C, then stop introducing argon;
[0026] (5.10) After the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank;
[0027] (5.11) The surface ultra-dense silicon carbide ceramic material blank in step (5.10) is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material.
[0028] As an improvement, in step (1), the mass ratio of silicon carbide to binder is 1:0.05-0.2, and the binder is one or more of phenolic resin, microcrystalline cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.
[0029] As an improvement, in step (2), the dispersant is one or more of polyvinyl alcohol, polyethylene glycol, tetramethylammonium hydroxide, hexamethylenetetramine; the surfactant is one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, alkyl alcohol amide, glycerol fatty acid ester; the defoaming agent is one or more of n-pentanol, isopentanol, n-hexanol, cyclohexanol; and the solvent is one or more of ethanol and water.
[0030] As an improvement, in step (5.7), the flow ratio of argon, hydrogen and chloroform is 100:100~60:10~1.
[0031] As an improvement, in step (5.4), a sufficient amount is impregnated until the difference between two weighings does not exceed 1-5%, and the number of impregnations is 2-10 times, preferably 2-7 times.
[0032] Beneficial effects: The composite material and preparation method proposed in the present invention have the following advantages compared with conventional ones:
[0033] (1) The present invention achieves the control of the porosity of the ceramic matrix 5-10 mm below the surface of the silicon carbide ceramic by adopting the steps of blank preparation, pre-sintering and surface sealing. The pores in the ceramic blank are fully exposed by pre-sintering, and the pores are further filled with silicon carbide precursor materials by vacuum impregnation during sealing. The voids are filled after high-temperature cracking, thereby reducing the porosity 5-10 mm below the ceramic surface.
[0034] (2) In the present invention, the pores on the surface of the prepared silicon carbide ceramic are sealed by chemical vapor deposition. The pores are first sealed by depositing silicon carbide ceramic in the pores, and then a continuous silicon carbide ceramic coating is formed on the surface of the substrate using the above-mentioned sealing points as anchor points. The pinning effect of the sealing points is used to improve the bonding strength of the ceramic coating.
[0035] (3) The present invention effectively improves the densification degree of the surface layer of silicon carbide ceramic components, reduces the porosity, and thereby improves its hardness, strength and service life by combining multiple methods. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention will be described clearly and completely below so that those skilled in the art can better understand the advantages and features of the present invention, thereby making a clearer definition of the protection scope of the present invention. The embodiments described in the present invention are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0037] The present invention discloses a method for preparing a surface ultra-dense silicon carbide ceramic material, comprising mixing raw silicon carbide and a binder in proportion to obtain a mixed powder; and then grinding the mixed powder in a grinder to obtain a fine powder with an average diameter of 20 to 300 μm. The ratio of silicon carbide to the binder is 1:0.05 to 0.2 by mass, and the binder is one or more of phenolic resin, microcrystalline cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.
[0038] Slurry preparation: add dispersant, surfactant, defoamer and solvent to the fine powder; then stir the mixture to form slurry; the dispersant is one or more of polyvinyl alcohol, polyethylene glycol, tetramethylammonium hydroxide, hexamethylenetetramine; the surfactant is one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, alkyl alcohol amide, glycerol fatty acid ester; the defoamer is one or more of n-pentanol, isopentanol, n-hexanol, cyclohexanol; the solvent is one or more of ethanol and water.
[0039] Preparation of green blank: adding the slurry into the mold and pressing and drying to form the ceramic green blank; then heating and drying the green blank, the drying temperature is 50-300°C, and the drying time is 0.1-2h;
[0040] Pre-sintering: pre-sinter the dried green billet at a temperature of 800 to 1300°C for 1 to 8 hours;
[0041] Surface sealing: Place the pre-sintered green blank in a vacuum impregnation tank and evacuate to a vacuum degree of 0.5 to 1.5 MPa; introduce the polycarbosilane solution into the impregnation tank and maintain the vacuum degree for 0.5 to 5 hours; take out the impregnated green blank and dry it at 80 to 200°C for 1 to 5 hours to remove the solvent; place the dried green blank in a chemical vapor deposition furnace, evacuate to a vacuum degree of 0.8 to 1.5 MPa, and maintain the vacuum degree.
[0042] The chemical vapor deposition furnace is heated to 800°C at a rate of 5-10°C / min and kept warm for 0.5-2h; argon gas is introduced into the chemical vapor deposition furnace at a flow rate of 10-200ml / min; after the argon gas is introduced for 10-30min, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 900-1300°C at a rate of 1-5°C / min and kept warm for 1-5h; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled, and after the temperature drops to 100°C, the introduction of argon gas is stopped; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of the argon gas, hydrogen gas and chloroform is 100:100-60:10-1.
[0043] The surface ultra-dense silicon carbide ceramic material of the present invention has a porosity of <0.1% and a density of 2.8-3.2 g / cm 3 , surface hardness is 2000~3000kg / mm 2 , three-point bending strength 250~300MPa, thermal conductivity 100~130W / (m·K), thermal expansion coefficient (3~5)×10 -6 / K.
[0044] Example 1
[0045] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.05 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 300 μm. The binder is phenolic resin and microcrystalline cellulose.
[0046] Add polyvinyl alcohol, polyethylene glycol, fatty alcohol polyoxyethylene ether, n-pentanol, cyclohexanol and ethanol to the fine powder, stir the mixture to make slurry. Add the slurry to the mold, and press dry to form a ceramic blank; then heat and dry the blank, the drying temperature is 300℃, the drying time is 0.1h; pre-sinter the dried blank, the pre-sintering temperature is 1300℃, and the sintering time is 1h; place the pre-sintered blank in a vacuum impregnation tank, and evacuate to a vacuum degree of 0.5MPa; introduce the polycarbosilane solution into the impregnation tank, and maintain the vacuum degree for 5h; take out the impregnated blank, and dry it at 80℃ for 5h to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 1.5MPa, and maintain the vacuum degree.
[0047] The chemical vapor deposition furnace is heated to 800°C at a rate of 5°C / min and kept warm for 2 hours; argon is introduced into the chemical vapor deposition furnace at a flow rate of 10 ml / min; after the argon is introduced for 10 minutes, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 900°C at a rate of 1°C / min and kept warm for 1 hour; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down, and the introduction of argon is stopped after the temperature drops to 100°C; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:100:10.
[0048] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 3.1 g / cm 3 , surface hardness is 2500kg / mm 2 , three-point bending strength 250MPa, thermal conductivity 100W / (m·K), thermal expansion coefficient 3.5×10 -6 / K.
[0049] Example 2
[0050] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.2 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 100 μm, and the binder is phenolic resin.
[0051] Add polyvinyl alcohol, polyethylene glycol, alkylphenol polyoxyethylene ether, cyclohexanol and ethanol to the fine powder, and stir the mixture to form a slurry. Add the slurry to the mold and pressurize and dry to form a ceramic blank; then heat and dry the blank to form, the drying temperature is 250℃, the drying time is 1.2h; pre-sinter the dried blank, the pre-sintering temperature is 800℃, and the sintering time is 8h; place the pre-sintered blank in a vacuum impregnation tank and evacuate to a vacuum degree of 1.5MPa; introduce the polycarbosilane solution into the impregnation tank and maintain the vacuum degree for 0.5h; take out the impregnated blank and dry it at 200℃ for 1h to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 0.8MPa, and maintain the vacuum degree.
[0052] The chemical vapor deposition furnace is heated to 800°C at a rate of 10°C / min and kept warm for 0.5h; argon is introduced into the chemical vapor deposition furnace at a flow rate of 200ml / min; after the argon is introduced for 30min, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 1200°C at a rate of 5°C / min and kept warm for 5h; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down to 100°C, and the introduction of argon is stopped; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:60:10.
[0053] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 2.8g / cm 3 , surface hardness is 2000kg / mm 2 , three-point bending strength 300MPa, thermal conductivity 130W / (m·K), thermal expansion coefficient 3×10 -6 / K.
[0054] Example 3
[0055] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.15 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 20 μm, and the binder is hydroxypropyl cellulose.
[0056] Add polyvinyl alcohol, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, n-pentanol, cyclohexanol and ethanol to the fine powder, and stir the mixture to form a slurry. Add the slurry to the mold, and press and dry to form a ceramic blank; then heat and dry the blank, the drying temperature is 50°C, and the drying time is 2 hours; pre-sinter the dried blank, the pre-sintering temperature is 1000°C, and the sintering time is 4 hours; place the pre-sintered blank in a vacuum impregnation tank and evacuate to a vacuum degree of 1MPa; introduce the polycarbosilane solution into the impregnation tank, and maintain the vacuum degree for 2 hours; take out the impregnated blank, and dry it at 100°C for 4 hours to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 1.0MPa, and maintain the vacuum degree.
[0057] The chemical vapor deposition furnace is heated to 800°C at a rate of 7°C / min and kept warm for 1h; argon is introduced into the chemical vapor deposition furnace at a flow rate of 110ml / min; after the argon is introduced for 20min, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 1300°C at a rate of 4°C / min and kept warm for 3h; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down, and the introduction of argon is stopped after the temperature drops to 100°C; after the chemical vapor deposition furnace is cooled to room temperature, the surface ultra-dense silicon carbide ceramic material blank is obtained by opening the furnace; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:60:1.
[0058] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 3.2g / cm 3 , surface hardness is 3000kg / mm 2 , three-point bending strength 280MPa, thermal conductivity 110W / (m·K), thermal expansion coefficient 5×10 -6 / K.
[0059] Example 4
[0060] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.05-0.2 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 20-300 μm. The binder is phenolic resin and hydroxypropyl cellulose.
[0061] Add polyvinyl alcohol, polyethylene glycol, fatty alcohol polyoxyethylene ether, cyclohexanol and water to the fine powder, and stir the mixture to form a slurry. Add the slurry to the mold and pressurize and dry to form a ceramic blank; then heat and dry the blank to form, the drying temperature is 180°C, the drying time is 0.9h; pre-sinter the dried blank, the pre-sintering temperature is 1000°C, and the sintering time is 6h; place the pre-sintered blank in a vacuum impregnation tank and evacuate to a vacuum degree of 1.0MPa; introduce the polycarbosilane solution into the impregnation tank and maintain the vacuum degree for 3.5h; take out the impregnated blank and dry it at 125°C for 2.5h to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 0.9MPa, and maintain the vacuum degree.
[0062] The chemical vapor deposition furnace is heated to 800°C at a rate of 7.5°C / min and kept warm for 1.6 hours; argon is introduced into the chemical vapor deposition furnace at a flow rate of 110 ml / min; after the argon is introduced for 16 minutes, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 1100°C at a rate of 3.5°C / min and kept warm for 1.8 hours; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down to 100°C, and the introduction of argon is stopped; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:75:3.5.
[0063] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 2.8-3.2 g / cm 3 , surface hardness is 2000~3000kg / mm 2 , three-point bending strength 250~300MPa, thermal conductivity 100~130W / (m·K), thermal expansion coefficient 4×10 -6 / K.
[0064] Example 5
[0065] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.15 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 20 to 300 μm. The binder is hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.
[0066] Add polyvinyl alcohol, polyethylene glycol, fatty alcohol polyoxyethylene ether, n-pentanol, cyclohexanol and water to the fine powder, and stir the mixture to form a slurry. Add the slurry to the mold, and press and dry to form a ceramic blank; then heat and dry the blank, the drying temperature is 175°C, and the drying time is 1.2 hours; pre-sinter the dried blank, the pre-sintering temperature is 1200°C, and the sintering time is 6 hours; place the pre-sintered blank in a vacuum impregnation tank and evacuate to a vacuum degree of 1.2MPa; introduce the polycarbosilane solution into the impregnation tank, and maintain the vacuum degree for 3.8 hours; take out the impregnated blank, and dry it at 1800°C for 4.0 hours to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 1.2MPa, and maintain the vacuum degree.
[0067] The chemical vapor deposition furnace is heated to 800°C at a rate of 7°C / min and kept warm for 1.0h; argon is introduced into the chemical vapor deposition furnace at a flow rate of 10-200ml / min; after the argon is introduced for 10-30min, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 1300°C at a rate of 2.5°C / min and kept warm for 4h; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down, and the introduction of argon is stopped after the temperature drops to 100°C; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:80:7.
[0068] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 3.0g / cm 3 , surface hardness is 2600kg / mm 2 , three-point bending strength 265MPa, thermal conductivity 118W / (m·K), thermal expansion coefficient 4.5×10 -6 / K.
[0069] Example 6
[0070] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.08 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 180 μm. The binder is phenolic resin.
[0071] Add polyvinyl alcohol, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, n-pentanol, cyclohexanol and water to the fine powder, and stir the mixture to form a slurry. Add the slurry to the mold, and press and dry to form a ceramic blank; then heat and dry the blank to form, the drying temperature is 115°C, the drying time is 0.85h; pre-sinter the dried blank, the pre-sintering temperature is 900°C, and the sintering time is 7h; place the pre-sintered blank in a vacuum impregnation tank and evacuate to a vacuum degree of 0.95MPa; introduce the polycarbosilane solution into the impregnation tank, and maintain the vacuum degree for 3.5h; take out the impregnated blank, and dry it at 170°C for 4.0h to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 1.1MPa, and maintain the vacuum degree.
[0072] The chemical vapor deposition furnace is heated to 800°C at a rate of 8°C / min and kept warm for 0.5 to 2 hours; argon is introduced into the chemical vapor deposition furnace at a flow rate of 190 ml / min; after the argon is introduced for 25 minutes, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 1300°C at a rate of 3°C / min and kept warm for 1.5 hours; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down, and the introduction of argon is stopped after the temperature drops to 100°C; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:75:5.5.
[0073] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 2.9g / cm 3 , surface hardness is 2400kg / mm 2 , three-point bending strength 275MPa, thermal conductivity 115W / (m·K), thermal expansion coefficient 3.5×10 -6 / K.
[0074] Example 7
[0075] The raw material silicon carbide and the binder are mixed in a mass ratio of 1:0.1 to obtain a mixed powder; the mixed powder is then placed in a grinder for grinding to obtain a fine powder with an average diameter of 240 μm. The binder is carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.
[0076] Add polyvinyl alcohol, polyethylene glycol, fatty alcohol polyoxyethylene ether, alkyl alcohol amide, n-pentanol, cyclohexanol and ethanol to the fine powder, and stir the mixture to make slurry. Add the slurry to the mold, and press and dry to form a ceramic blank; then heat and dry the blank, the drying temperature is 240℃, and the drying time is 0.6h; pre-sinter the dried blank, the pre-sintering temperature is 1100℃, and the sintering time is 5.5h; place the pre-sintered blank in a vacuum impregnation tank and evacuate to a vacuum degree of 1.4MPa; introduce the polycarbosilane solution into the impregnation tank, and maintain the vacuum degree for 3.6h; take out the impregnated blank, and dry it at 120℃ for 4h to remove the solvent; put the dried blank into a chemical vapor deposition furnace, evacuate to a vacuum degree of 0.9MPa, and maintain the vacuum degree.
[0077] The chemical vapor deposition furnace is heated to 800°C at a rate of 8°C / min and kept warm for 1.4 hours; argon is introduced into the chemical vapor deposition furnace at a flow rate of 140 ml / min; after the argon is introduced for 15 minutes, a mixed gas of hydrogen and chloroform is introduced into the chemical vapor deposition furnace; the chemical vapor deposition furnace is heated to 1000°C at a rate of 3°C / min and kept warm for 4 hours; after completion, the introduction of hydrogen and chloroform is stopped, and the furnace is cooled down to 100°C, and the introduction of argon is stopped; after the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; the surface ultra-dense silicon carbide ceramic material blank is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material. Wherein, the flow ratio of argon, hydrogen and chloroform is 100:60:2.
[0078] The obtained surface ultra-dense silicon carbide ceramic material has a porosity of <0.1% and a density of 2.9g / cm 3 , surface hardness is 2200kg / mm 2 , three-point bending strength 270MPa, thermal conductivity 115W / (m·K), thermal expansion coefficient 3.2×10 -6 / K.
[0079] 2. Experimental and test data
[0080] 1.1 Experimental test on density and porosity of ceramic blanks with different immersion times
[0081] The experimental group is: different processes with different impregnation times are selected to study the density, surface hardness and porosity of silicon carbide ceramics, and other parameters are the same. The preparation method of the present invention is selected to prepare the surface ultra-dense silicon carbide ceramic material of the experimental group, and then multiple groups of ceramic samples are taken to perform performance experiments, as shown in Table 1.
[0082] Table 15 Surface porosity of the surface ultra-dense silicon carbide ceramic materials prepared in experimental groups 1-5
[0083]
[0084] As shown in Table 1, it can be obtained that the increase in the number of impregnations is conducive to increasing the density of the ceramic material and reducing the porosity. After 5 impregnations, the density is already high and the porosity is already low, meeting the process requirements. The number of impregnations is 2-15 times, preferably 2-7 times. The actual number of impregnations is determined by: the difference in weight between the two impregnations is no more than 1-5% as the standard for stopping the impregnation.
[0085] 1.2 Experimental test on surface porosity at different chemical vapor deposition times
[0086] The experimental group is: different chemical vapor deposition processes are selected to study the surface hardness and porosity of silicon carbide ceramics, and other parameters are the same. The preparation method of the present invention is selected to prepare the surface ultra-dense silicon carbide ceramic material of the experimental group, and then multiple groups of ceramic samples are taken to perform performance experiments. The results are shown in Table 2.
[0087] Table 2 Surface porosity of ultra-dense silicon carbide ceramic materials at different deposition times
[0088]
[0089] As shown in Table 2, it can be obtained that the increase of deposition time is beneficial to reduce the porosity and improve its surface hardness.
[0090] In summary, the present invention achieves the control of the surface porosity of silicon carbide ceramics by adopting the steps of blank preparation, pre-sintering and surface sealing. Pre-sintering is used to expose the pores in the ceramic blank, vacuum impregnation is used to fill the silicon carbide precursor and initially seal the pores to improve the densification degree, and chemical vapor deposition is used to perform secondary pore sealing and form a continuous silicon carbide ceramic coating on the surface, thereby obtaining a silicon carbide ceramic material with a high degree of surface densification and low porosity.
[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A surface ultra-dense silicon carbide ceramic material, characterized in that: The ultra-dense silicon carbide ceramic material is formed by first sintering silicon carbide powder and then sealing the pores through surface treatment to form the surface ultra-dense silicon carbide ceramic material.
2. The surface ultra-dense silicon carbide ceramic material according to claim 1, characterized in that: The porosity of the surface ultra-dense silicon carbide ceramic material is less than 0.1%, and the density is 2.8-3.2 g / cm 3 , surface hardness is 2000~3000kg / mm 2 , three-point bending strength 250~300MPa, thermal conductivity 100~130W / (m·K), thermal expansion coefficient (3~5)×10 -6 / K.
3. A method for preparing a surface ultra-dense silicon carbide ceramic material, characterized in that: The following steps are involved: (1) Powder preparation (1.1) Mixing the raw material silicon carbide and the binder according to a certain proportion to obtain a mixed powder; (1.2) Grinding the mixed powder in a grinder to obtain fine powder with an average diameter of 20 to 300 μm; (2) Slurry preparation (2.1) adding a dispersant, a surfactant, a defoaming agent and a solvent to the fine powder obtained in step (1.2); (2.2) stirring the mixture in step (2.1) to form a slurry; (3) Preparation of green billet (3.1) adding the slurry in step (2) into a mold and pressing and drying to form a ceramic green body; (3.2) heating and drying the green blank in step (3.1) at a drying temperature of 50 to 300° C. for a drying time of 0.1 to 2 h; (4) Pre-sintering Pre-sintering the dried green blank in step (3) at a temperature of 800 to 1300° C. for a sintering time of 1 to 8 hours; (5) Surface sealing (5.1) The pre-sintered green blank in step (4) is placed in a vacuum impregnation tank and evacuated to a vacuum degree of 0.5 to 1.5 MPa; (5.2) introducing the polycarbosilane solution into the impregnation tank of step (5.1) and maintaining the vacuum degree for 0.5 to 5 hours; (5.3) taking out the impregnated green body in step (5.2), and drying it at 80-200° C. for 1-5 hours to remove the solvent; (5.4) Repeat steps (5.2) to (5.3) to allow the green body to absorb a sufficient amount of polycarbosilane; (5.5) placing the dried green blank in step (5.4) into a chemical vapor deposition furnace, evacuating the furnace to a vacuum degree of 0.8 to 1.5 MPa, and maintaining the vacuum degree; (5.6) heating the chemical vapor deposition furnace in step (5.5) to 800° C. at a rate of 5 to 10° C. / min and maintaining the temperature for 0.5 to 2 h; (5.7) introducing argon gas into the chemical vapor deposition furnace of step (5.6) at a flow rate of 10 to 200 ml / min; (5.8) After the argon gas is passed through step (5.7) for 10 to 30 minutes, a mixture of hydrogen and chloroform is passed through the chemical vapor deposition furnace; (5.9) raising the temperature of the chemical vapor deposition furnace in step (5.8) to 900-1300° C. at a rate of 1-5° C. / min and maintaining the temperature for 1-5 h; (5.10) After step (5.9) is completed, stop introducing hydrogen and chloroform, and cool the furnace to 100°C, then stop introducing argon; (5.11) After the chemical vapor deposition furnace is cooled to room temperature, the furnace is opened to obtain a surface ultra-dense silicon carbide ceramic material blank; (5.12) The surface ultra-dense silicon carbide ceramic material blank in step (5.11) is mechanically polished to obtain a surface ultra-dense silicon carbide ceramic material.
4. The method for preparing the surface ultra-dense silicon carbide ceramic material according to claim 3, characterized in that: In step (1), the ratio of silicon carbide to binder is 1:0.05-0.2 by mass, and the binder is one or more of phenolic resin, microcrystalline cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.
5. The method for preparing the surface ultra-dense silicon carbide ceramic material according to claim 3, characterized in that: In step (2), the dispersant is one or more of polyvinyl alcohol, polyethylene glycol, tetramethylammonium hydroxide, hexamethylenetetramine; the surfactant is one or more of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, alkyl alcohol amide, glycerol fatty acid ester; the defoamer is one or more of n-pentanol, isopentanol, n-hexanol, cyclohexanol; and the solvent is one or more of ethanol and water.
6. The method for preparing the surface ultra-dense silicon carbide ceramic material according to claim 3, characterized in that: In step (5.7), the flow ratio of argon, hydrogen and chloroform is 100:100-60:10-1.
7. The method for preparing the surface ultra-dense silicon carbide ceramic material according to claim 3, characterized in that: In step (5.4), a sufficient amount is impregnated until the difference between two weighings does not exceed 1-5%, and the number of impregnations is 2-10 times.
Citation Information
Patent Citations
SiC hollow sphere and preparation method of same
CN107602127A
Silicon carbide ceramic and preparation method thereof
CN116410013A
C / SiC composite material, anti-ablation protection piece and application of anti-ablation protection piece
CN117964375A
Silicon carbide ceramic as well as preparation method and application thereof
CN118271095A
Process for producing a furnace component
DE3701691A1
Cited By
SiC edge ring and preparation method and application thereof
CN119530756A